The Effect Of Load Balancing And Failover Of Two Wide Area Networks With Per Connection Classifier Method On Qos Throughput, Packet Loss, Qos Delay, And Qos Jitter: Pengaruh Load Balancing dan Failover Dua Wide Area Network Dengan Metode Per Connection Classifier pada QoS Throughput, Packet Loss, QoS delay, dan QoS jitter - Hariadi, Fajar; Alfa Ray Leo Lede, Pingky; Melvy Kalaway, Umbu (JOINCS (Journal of Informatics, Network, and Computer Science), 2021)
This study discussed the design and implementation of load balancing of two WANs so that the traffic load and bandwidth provided by both WANs could be used equally. The methods used in this research were observation and identification, network topology design, implementation, and testing. This study found that load balancing could divide the network load to all available gateways so that there was no overload on the network used by visitors. After implementing load balancing, the network throughput parameter increased 1.51% compared to the Indihome 1 network and 7.5% compared to the Indihome 2 network. The packet loss parameter increased by 99% compared to the Indihome 1 network and increased 90% compared to the Indihome 2 network. Network delay decreased by 1.33% compared to the Indihome 1 network, and decreased by 1.5% compared to the Indihome 2 network. The Network jitter parameter decreased by 0.93% compared to the Indihome 1 network and decreased by 1.54% compared to the Indihome 2 network.